Outcomes after Robotic Ventral Hernia Repair: A Study of 21, 565 Patients in the State of New York. Issue 6 (June 2018) - Altieri, Maria S.; Yang, Jie; Xu, Jianjin; Talamini, Mark; Pryor, Aurora; Telem, Dana A.
The purpose of our study is to assess outcomes following robotic ventral hernia (RVH) repair. The New York Statewide Planning and Research Cooperative System administrative database was used to identify all patients undergoing laparoscopic ventral hernia (LVH) and RVH between 2010 and 2013. Outcome measures including complications, hospital length of stay (HLOS), 30-day readmissions, and 30-day emergency department (ED) visits were compared. Propensity score (PS) analysis was used to estimate the adjusted marginal differences between patients who underwent robotic-assisted and laparoscopic procedures. There were 20, 896 LVH and 679 (3.2%) RVH repairs. Initial univariate analysis demonstrated that patients undergoing RVH had worse outcomes in terms of complications (20.18% vs 10.56%, P < 0.0001), longer HLOS (4.32 vs 2.19 days, P = 0.0023), higher rates in 30-day readmissions (9.28% vs 5.06%, P < 0.0001), and 30-day ED visits (14.43% vs 10.46%, P < 0.0001). Following PS analysis, which accounts for all patient associated variables, there was no difference found in 30-day readmission or 30-day ED visits between RVH and LVH (P = 0.2760 and 0.2043, respectively). Patients undergoing RVH had a significantly shorter HLOS (P < 0.0001) and lower rate of complications (P = 0.0134). Following PS analysis, this study demonstrates that RVH may be associated with shorter HLOS and lower complication rate. Further studies are necessary to compare laparoscopic and robotic approaches for ventral hernia.